SOSIALISASI PENANGGULANGAN STUNTING MELALUI PERENCANAAN SISTEM PERSAMPAHAN DI DESA PASAR RAWA, KECAMATAN GEBANG KABUPATEN LANGKAT - Sausan Alfiyyah; Dinda Putri Mulya; Dany Syahputra; Rahmadhani Fitri (Arsil Media, 2024)
The purpose of this service activity is to overcome stunting in Pasar Rawa village. Stunting is a chronic nutritional problem that is still a serious health issue. One of the indirect causes of stunting is an unhealthy environment, especially poor waste management. This activity is also to design a waste management plan as a preventive effort in reducing stunting in Pasar Rawa Village, Gebang District, Langkat Regency. The methods used include social approaches, field observations, and direct interviews with local communities. The results of the activity show that community awareness of the importance of waste management is still low, and polluted environmental conditions contribute to the increased risk of infection in toddlers. Through the socialization program and the implementation of a household-based waste management system, the community began to understand the link between a clean environment and stunting prevention. This activity is expected to have a long-term impact in creating a healthy environment and improving the quality of life of the village community.